Al Lawāsiq Fil Af’āl Ar Rubā’iyyah - Muhammad Taufiq Fadhlurrahman (University of Darussalam Gontor, 2019)
AbstractThe word in Arabic has a free meaning if it has not been affixed to any letter, if there are affixes in it then it becomes bound, and changes its shape, and becomes narrower in meaning. This statement can be seen in the following example: